Running cross-correlation using bitstream processing - Lande,TS; Constandinou,TG; Burdett,A; Toumazou,C (Electronics Letters, 2007)
A novel architecture for running cross-correlation and convolution using bitstream processing is proposed. The computationally intensive multiplications inherent in cross-correlation and convolution are replaced by simple logic operations (AND XOR) using bitstream representation. The reduced complexity enables compact and energy efficient silicon solutions suitable for small, portable devices such as wearable heartbeat detecting electronics embedded in the actual ECG patch.